A discourse analysis of hand hygiene policy in NHS Trusts. Issue 4 (July 2015) - Cole, Mark
Introduction: Healthcare-associated infection is a major patient safety concern. Hand hygiene is widely thought to be the single most important measure to affect reductions but compliance is problematic. Producing policies that clearly outline the responsibilities of staff is seen as a key way to instil accountability and improve performance. Objectives: The purpose of this study is to examine the discourse of hand hygiene policies across 359 NHS Trusts in England and consider the implications for practice. Method: The data were examined by combining the techniques of corpus linguistics with critical discourse analysis to generate keywords and concordance lines and then to make an interpretation what this may mean for the healthcare worker. Results: High frequency words such as 'must', 'should', 'will', 'responsible', 'compliance' and 'audit' suggest a tone that is authoritative and unyielding. This creates a fractured relationship between those who produce policies and the healthcare workers who need to comply with them. Conclusion: In their intentions to advance patient care policy, producers take little account of the messy, contextual factors that make the recommendations challenging to implement in daily practice. Firstly, Trusts should consider the use language that acknowledges the dynamic nature of practice and, secondly, cease using audit data as an indicator of performance as the conditions under which information is collected lacks reliability.